TEHLİKELİ SALGIN HASTALIKLARLA ANAYASALMÜCADELEYE GİRİŞ - (:unkn) unknown (My University, 2020)
COVID-19 salgını sırasında kaleme alınan bu makale beş başlıktanoluşmaktadır.Birinci başlıkta, Anayasa’da yer alan “tehlikeli salgın hastalık” çözümlenmiştir. Bu bölümde, “tehlikeli” kavramının yaygın ölüm veyaölüm tehdidi bulunan durumlara işaret ettiği; salgın kavramının “epidemi” anlamına geldiği; hastalık kavramının ise hayvan hastalıklarını kapsamadığı sonucuna ulaşılmıştır. İkinci başlıkta, sağlık hukukunun anayasal tarihi genel hatlarıylaortaya konmuştur. Bu bölümde Cumhuriyetin ilk yıllarındaki atılımolumlu bulunmuş fakat gerekli hukuki güncellemelerin yapılmadığı sonucuna varılmıştır.Üçüncü başlıkta tehlikeli salgın hastalıkların karşılaştırmalı anayasa hukukundaki yeri tespit edilmiştir. Başta seyahat özgürlüğü ile serbestseçim hakkı olmak üzere Anayasa’da birçok hak ve özgürlük için genelsağlığın korunması şeklinde sınırlama nedeninin bulunmamasının birsorun teşkil ettiği sonucuna ulaşılmıştır.Dördüncü başlıkta, Umumi Hıfzıssıhha Kanunu’nun hükümleri,konuyla ilgili temel haklar yönünden incelenmiş ve boşluklar tespitedilmiştir.Beşinci başlıkta ise Türkiye’deki OHAL rejimi anlatışmış, bu rejimde-uygulamanın aksine- kanunilik ilkesinin geçerli olduğu iddiaedilmiştir. Temel savım, OHÂL’de dahi OHÂL Kanunu’nun çizdiği sınırların dışına çıkılamayacağıdır. Bu bölümde bu sav gerekçelendirilmiş,ayrıca (sokağa çıkma yasağına dahi olanak tanımayan) OHAL Kanunu’nun tehlikeli salgın hastalıklara karşı yetersizliği ortaya konulmuştur.

his paper, written during the Covid-19 pandemic, consists of five parts. In the first part, the concept of a “dangerous epidemic disease” enshrined in the Turkish Constitution has been analysed. It is concluded that the concept of dangerous refers to situations with widespread death or death threats, the concept of “salgın” means epidemic, and the con?cept of disease does not cover animal diseases. In the second part, the constitutional history of Turkish health law was outlined in general terms. In this part, it was determined that the breakthrough in the first years of the Republic was in a positive direc?tion; however, it was found that the necessary legal updates were not made in the years to follow. In the third part, “dangerous epidemics” in comparative constitu?tional law has been reviewed. In this context, it was concluded that thlack of the reason of “protection of general health” in some of the rele?vant articles (especially for the freedom of movement and the right to free election) of the Constitution poses some problems. In the fourth part, the provisions of the General Hygiene Act (1930) are examined in terms of fundamental rights and some legal gaps in the Code are found. In the fifth part, the state of emergency regime in Turkey was de?scribed and it was claimed that the lawfulness principle is still valid in the regime as opposed to ongoing practices. The main argument in this section is that the limits set by the State of Emergency Act (1983) cannot be exceeded even in the state of emergency. Moreover, in this section the reasons for this argument were explained in detail, and the inadequacy of the relevant Act (which does not even permit curfew) against danger?ous epidemics.
THE CONSTITUTIONAL STRUGGLE AGAINST DANGEROUS EPIDEMIC DISEASES